Sensory capabilities and food capture of two small copepods, Paracalanus parvus and Pseudocalanus sp. (27th August 2013) - Tiselius, Peter; Saiz, Enric; Kiørboe, Thomas
Abstract : Detection, handling, and selection of prey are key features of suspension‐feeding copepods. Using high‐speed video, we determined detection distances and durations of all elements of the food gathering process in two small calanoid copepods, Paracalanus parvus and Pseudocalanus sp. Animals were freely swimming and presented with various phytoplankton species with equivalent spherical diameters ranging from 7 µm to 33 µm. Prey detection occurred very close—within a few cell radii—to the second antennae (53% of the cases) or the maxilliped (42%). There was no effect of prey size on detection distance, but larger prey caused a significantly longer handling time. Post‐detection processing of the cells was exceedingly fast. The time from detection to the cell being placed at the mouth lasted 35 ± 19 ms and rejection of unwanted cells 61 ± 21 ms. Grooming of antennules and carapace occurred intermittently and lasted 215–227 ms. The weak feeding current and fast response of the copepods allowed ample time for detection of cells entrained in the feeding current and no distant olfaction was observed. Modeled effect of cell size on cell surface concentration of cue chemicals show that only cells with a radius larger than ∼ 15 µm may be detected chemically and that only very much larger and/or very leaky cells can be detected at distance. Copepods have elaborate and exceedingly fast handling techniques that allow effective prey detection and capture, but there is no evidence of remote chemically mediated sensing when feeding on algal cells up to a size of 35 µm.